Mengontrol Pengumpulan Data Stok dan Penentuan Harga di Sistem Inventaris - Rizal Hafizh; Irma Handayani (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2023)
Abstract — Data collection regarding the activities and transactions of products entering and leaving a company is intimately linked to inventory management in businesses. CV. Amalia Buku, is an individual company located on Jl. Juminahan, Purwokinanti, Pakualaman, which operates in the field of book sales. Recording incoming and outgoing goods inventory on CV. Amalia Books are still done by writing them down in notebooks and this causes the notes to be lost or damaged. Based on these problems, this research designs and builds a mobile web-based book inventory system. This system was built using the RAD (Rapid Application Development) method and uses Laravel framework, while mobile with Android Studio whose programming language is Kotlin. The data processed in this system is incoming book data, outgoing book data, book stock data, and user data , who can collect data on stock reports, and incoming book reports and outgoing book reports. The results of this research produce a mobile web-based book inventory system that can be used by CVs. Amalia Books.